DPP signaling controls development of the lamina glia required for retinal axon targeting in the visual system of Drosophila. - Yoshida, S.; Soustelle, L.; Giangrande, A.; Umetsu, D.; Murakami, S.; Yasugi, T.; Awasaki, T.; Ito, K.; Sato, M.; Tabata, T. (Development, 2005)
The Drosophila visual system consists of the compound eyes and the optic ganglia in the brain. Among the eight photoreceptor (R) neurons, axons from the R1-R6 neurons stop between two layers of glial cells in the lamina, the most superficial ganglion in the optic lobe. Although it has been suggested that the lamina glia serve as intermediate targets of R axons, little is known about the mechanisms by which these cells develop. We show that DPP signaling plays a key role in this process. dpp is expressed at the margin of the lamina target region, where glial precursors reside. The generation of clones mutant for Medea, the DPP signal transducer, or inhibition of DPP signaling in this region resulted in defects in R neuron projection patterns and in the lamina morphology, which was caused by defects in the differentiation of the lamina glial cells. glial cells missing/glial cells deficient (gcm; also known as glide) is expressed shortly after glia precursors start to differentiate and migrate. Its expression depends on DPP; gcm is reduced or absent in dpp mutants or Medea clones, and ectopic activation of DPP signaling induces ectopic expression of gcm and REPO. In addition, R axon projections and lamina glia development were impaired by the expression of a dominant-negative form of gcm, suggesting that gcm indeed controls the differentiation of lamina glial cells. These results suggest that DPP signaling mediates the maturation of the lamina glia required for the correct R axon projection pattern by controlling the expression of gcm.